Profoundly Changed: The Homecoming of Veterans from Iraq and Afghanistan - Kelly Wadsworth (The University of Alabama, 2022)
This phenomenological research study, conducted from 2017 to 2018, rigorously and methodologically investigated Iraq and Afghanistan (OIF/OEF) veterans' first-person accounts of their experiences of profound change after war. This study explored the existential themes of homecoming, betrayal, grief, guilt, meaning, and truth-telling through the lens of OIF/OEF veterans. This existential investigation built on the methods of Husserl's phenomenology, which explored human consciousness, and Heidegger and others, who deepened the phenomenological exploration to address the question of human existence. Key to the investigation of human phenomena is allowing the core encounter to emerge through rich, authentic description. In this study, OIF/OEF veterans described an experience in which they recognized that they had been profoundly changed by war. In-person interviews were recorded and transcribed. Data was analyzed using Colaizzi's (1978) seven-step approach. The findings highlighted how profound change after war was a matrix of psychological and spiritual expansion for both the individuals and their communities. The fundamental structure of this phenomenon had three essential facets. First, experience, awareness, and impact collectively constituted one another in a circle of influence. Second, a before-deployment self stood in stark contrast to an expanded after-deployment self. Finally, profound change was enduring and had wide-sweeping implications throughout many levels of each veteran's life. Psychological-spiritual growth may result in symptomatic behaviors that are easily attributed to psychological disorders. These results also illuminate the need for social support at the community level as well as the need for veterans to cultivate self-awareness as part of the transition process.